SAVE NOT DESTROY: ARCHITECTURAL MONUMENT AND URBAN PLANNING OF HALYCH. HOUSE OF THE ROMAN CATHOLIC PARISH (END OF THE 19TH – FIRST HALF OF THE 20TH CENTURY) - CHEMERYNSKYI, Andrii (Halych. Scientific work collection, 2022)
The article focuses on the valuable object of architecture and urban planning of the city of Halych, describes its history, architectural features; famous people who built and visited this building. Attention is drawn to the threat of its destruction through the proposed construction of a residential complex, and the need for its preservation by local self-government bodies and monument protection structures is emphasized.